# (2x+3)+(4x-2)=

## Simple and best practice solution for (2x+3)+(4x-2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (2x+3)+(4x-2)= equation:

Simplifying
(2x + 3) + (4x + -2) = 0
Reorder the terms:
(3 + 2x) + (4x + -2) = 0
Remove parenthesis around (3 + 2x)
3 + 2x + (4x + -2) = 0
Reorder the terms:
3 + 2x + (-2 + 4x) = 0
Remove parenthesis around (-2 + 4x)
3 + 2x + -2 + 4x = 0
Reorder the terms:
3 + -2 + 2x + 4x = 0
Combine like terms: 3 + -2 = 1
1 + 2x + 4x = 0
Combine like terms: 2x + 4x = 6x
1 + 6x = 0
Solving
1 + 6x = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-1' to each side of the equation.
1 + -1 + 6x = 0 + -1
Combine like terms: 1 + -1 = 0
0 + 6x = 0 + -1
6x = 0 + -1
Combine like terms: 0 + -1 = -1
6x = -1
Divide each side by '6'.
x = -0.1666666667
Simplifying
x = -0.1666666667